External stress, formaldehyde, and schizophrenia: a new mouse model for mental illness research - Junhao Cheng; Zihui Sun; Hao Zhang; Danrui Zhao; Panpan Wang; Haishu Chen; Wanjia Lyv; Qiangfeng Deng; Yuanyu Fu; Xingzhou Lyv; Tingting Gao; Jinan Xu; et al. (Schizophrenia)
Abstract Although MK801-induced NMDA receptor (NMDAR) hypofunction mimics schizophrenia symptoms, the exact factors causing NMDAR inhibition are unknown. Unexpectedly, external stress elicits formaldehyde (FA) generation; FA can induce depression and cognitive impairments by blocking NMDARs. This study explores using FA injection to establish a schizophrenia-like model in mice. Here, we reported that external stress-derived FA induces schizophrenia-like behaviors. Four experimental methods were used to induce schizophrenia-like symptoms in wild-type mice: double electrode stimulation of the ventral tegmental area (VTA), microinjection of FA or tetrahydroisoquinoline (TIQ) into the VTA, and intraperitoneal injection of MK801. Then the metabolic levels of FA and dopamine (DA) in the prefrontal cortex (PFC) and VTA were quantified using ELISA kits. We found that external stress-electrical stimulation via VTA caused schizophrenia-like behaviors, including despairing behavior as measured by the tail suspension test, anhedonia as evaluated by the sucrose preference test, stereotypical behavior as assessed by the marble burying test (MBT), anxiety-like behavior as measured by the open-field test and memory deficit as detected by the Y-maze. These behaviors correlated with increased DA and TIQ levels in the VTA and decreased DA levels in the PFC. High-resolution mass spectrometry (HRMS) and high-performance liquid chromatography (HPLC) confirmed TIQ formation from FA and DA. Furthermore, injecting TIQ into the VTA induced schizophrenia-like symptoms in mice, marked by higher FA and lower DA levels in the PFC than control mice. Strikingly, injecting FA into the VTA as well as administering MK-801 induced schizophrenia-like behaviors associated with reduced DA levels and low activity of tyrosine hydroxylase (TH) and monoamine oxidase (MAO) in the PFC. Hence, microinfusion of FA into the VTA can be used to prepare schizophrenia-like changes mouse model, suggesting that stress-derived FA may act as an endogenous trigger of schizophrenia-like changes.